Enhancing the Security of Information Systems Using Iot Technology - Gaata, Methaq Talib; Mohialden, Yasmin Makki; Mahmood Hussien , Nadia (Newinera Publisher, 2024)
Psychiatric patient information system that is used in most mental health clinics is very important in dealing with patient records. However, the safety of such systems is a major issue since information being processed in such systems is often sensitive. This paper offers a new way of boosting the security of the Mentcare information system via the incorporation of IoT technology. The following figure demonstrates the components of the proposed security framework of the system which uses highly secure password generation algorithms that enable the system to generate passwords of different levels of complexities depending on the user’s preference. Such improvements guarantee exclusive safeguard mechanisms against illegitimate access since IoT provides a way of passing secure passwords to the right individuals in real-time. That has resulted in the overall decreases in hacking attempts by the unauthorized access and enhanced the encryptions that meet GDPR and HIPAA standards and practices fully integrated with IoT technology. Also, general enhancements have been made on Mentcare system with regard to the ease and speed in generating password, system response time and user satisfaction. In light of these findings, this study reaffirms the need to have IoT-advanced security protocols for medical information systems especially in mental health care where patients’ information needs to be well protected. The conclusions prove that in addition to increasing security, the proposed system optimizes the process of its functioning, which confirms that it is necessary to apply it to protect the health care information.